1995
DOI: 10.1063/1.359171
|View full text |Cite
|
Sign up to set email alerts
|

Raman scattering studies of surface modification in 1.5 MeV Si-implanted silicon

Abstract: Cleaved Si(111) 2×1 surface studied by MeV ion scattering

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 24 publications
3
20
0
Order By: Relevance
“…The sample surface can also act as a sink for vacancies. The recombination processes or the role of the surface can also be responsible for the saturation of damage in the SR where no increase in damage is observed beyond a fluence of 5ϫ10 13 ions/cm 2 . The distribution of the damage profile is governed by the balance between the production of damage and the annealing of defects.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The sample surface can also act as a sink for vacancies. The recombination processes or the role of the surface can also be responsible for the saturation of damage in the SR where no increase in damage is observed beyond a fluence of 5ϫ10 13 ions/cm 2 . The distribution of the damage profile is governed by the balance between the production of damage and the annealing of defects.…”
Section: Resultsmentioning
confidence: 99%
“…This result is surprising since the formation of amorphous structures should alleviate the stress. 13,21 It is important to note that in this Raman study results are obtained from a probing depth of ϳ770 nm, the total penetration depth of the laser. In another study, 12 we have reported the variations in stress as a function of depth where a compressive stress near the surface evolves to a tensile stress in the implanted zone, which indicates a separation of vacancy-and interstitial-related defects with depth.…”
Section: Resultsmentioning
confidence: 99%
“…The implantation of Si + ions into a silicon wafer with an energy of 1.5 MeV and doses ranging from 1×10 11 to 1×10 15 Si + ions/cm 2 lead to compressive residual stresses up to 120 MPa in the surface layer. [31] If the shift was solely caused by internal stresses it would correspond to tensile stresses ranging from 2.5 to 10 GPa. [32] Tensile stresses in this range would most likely lead to fracture of the lamella.…”
Section: Discussionmentioning
confidence: 99%
“…4 -45 Raman scattering has also been performed on Si nanocrystals prepared by other methods, such as plasma transport, 15,46 gas evaporation technique, 47 reactive sputtering technique, 48 molecular beam deposition, 49 laser annealing of a-Si : H samples, 50 plasma-enhanced chemical vapor deposition 51 and surface modification by implantation. 40 From the observed phonon shifts the particle sizes have been estimated mostly using the confinement model CM-I (Eqn (4)) with Gaussian weighting functions or with the weighting function W r, L D sin ˛r /˛r, by analogy with the ground state of an electron in a hard sphere. 17,18 In some cases the nanocrystal sizes were determined independently by other methods.…”
Section: Size Determination By Raman Scatteringmentioning
confidence: 99%